Вы находитесь на странице: 1из 2

(I )

3x 5 y = 11

1. 2 x + 3 y = 20

1) (7;2) ;
2) (7;2) ;

3) (2;1) ;
4) (2;1) .

3 2

= 7 4 8
5 3 4 :
2.
1) 0;
2) 26;
3) 301;
4) 53.
3. (2; 3) (3; 1),
1) (5; 4);
2) (5; 4);
3) (1; 2);
4) (1; 4).

2 2

=1
9 25

4.
1) ;
2) ;
3) ;
4) .

5. , 2,

6x2 + x 1
lim
2
x
4
+
2
x
+
3
x
1)
2 + 4x
lim
x
2 3 ;
2)

1 + 2x2
lim
3
x
1

x
3)
;
4)

lim
x

2x
2x + 1 .
y=

6.

1 ln x
2
x
1)
;
1 + ln x
2
x
2)
;
1
3) x ;
1 + ln x
x ;
4)

ln x
x

7.
1) 0;
2) 2,5;

3
( x + 2 x)dx

2
3;

3)
4) 1,5.

2
8. f ( x ) = 3 x 2 x + 4

3
2
1) x x + 4 x + C ;
2) 6 x 2 ;
3x 3
2x2 + 4x + C
3) 2
;
3
2
4) x x + 4 + C ;